Magnetic resonance elastography to study the effect of amyloid plaque accumulation in a mouse model. Issue 4 (5th April 2022) - Palotai, Miklos; Schregel, Katharina; Nazari, Navid; Merchant, Julie P.; Taylor, Walter M.; Guttmann, Charles R. G.; Sinkus, Ralph; Young‐Pearse, Tracy L.; Patz, Samuel
Abstract: Background and Purpose: Biomechanical changes in the brain have not been fully elucidated in Alzheimer's disease (AD). We aimed to investigate the effect of β‐amyloid accumulation on mouse brain viscoelasticity. Methods: Magnetic resonance elastography was used to calculate magnitude of the viscoelastic modulus (|G*|), elasticity (Gd ), and viscosity (Gl ) in the whole brain parenchyma (WB) and bilateral hippocampi of 9 transgenic J20 (AD) mice (5 males/4 females) and 10 wild‐type (WT) C57BL/6 mice (5 males/5 females) at 11 and 14 months of age. Results: Cross‐sectional analyses showed no significant difference between AD and WT mice at either timepoints. No sex‐specific differences were observed at 11 months of age, but AD females showed significantly higher hippocampal |G*| and Gl and WB |G*|, Gd, and Gl compared to both AD and WT males at 14 months of age. Similar trending differences were found between female AD and female WT animals but did not reach significance. Longitudinal analyses showed significant increases in hippocampal |G*|, Gd, and Gl, and significant decreases in WB |G*|, Gd, and Gl between 11 and 14 months in both AD and WT mice. Each subgroup showed significant increases in all hippocampal and significant decreases in all WB measures, with the exception of AD females, which showed no significant changes in WB |G*|, Gd, or Gl . Conclusion: Aging had region‐specific effects on cerebral viscoelasticity, namely, WB softening and hippocampal stiffening. Amyloid plaque deposition may have sex‐specific effects, which require further scrutiny.